Aspek Biologi Ikan Silais (Kryptopterus hexapterus Bleeker 1851) - Rina Sari; Khairul Khairul (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to determine the biological aspects of silais in Bilah River. The method used is exploratory with the determination of fish sampling points based on the fishing area carried out by fishermen (purposive sampling). The fishing gear used to take fish samples is a splint. Fish samples caught were measured for total length and weight. The results showed that the size class of fish data was divided into three sizes: small (9-11.9 cm) with 8 males and 29 females, medium (12-14.9 cm) with 7 males and 16 females large. (15-17.9 cm) only 2 females. The relationship between length and weight of fish found was b = 0.19 and R2 = 0.82. The sex ratio of silais fish (male and female) obtained is 0.34:1. In conclusion, the biological aspect of silais fish in Bilah River is categorized as quite good. Keywords: Biological Aspects, Kryptopterus hexapterus, Bilah River